Validation of selective use of intraoperative PTH monitoring in parathyroidectomy. Issue 1 (December 2017) - Thielmann, Alexandra; Kerr, Paul
Abstract Background The objective of this study was to validate our approach of treating primary hyperparathyroidism using sestamibi scan directed parathyroidectomy, without routine use of intraoperative parathyroid hormone measurements (ioPTH). Methods We prospectively established a protocol limiting the use of ioPTH to patients with negative or equivocal sestamibi scans, and those who had risk factors for multi-gland disease. We then performed a retrospective review to determine our disease control rate. Results 128 patients underwent sestamibi-guided parathyroidectomy without (111/128 = 87%) or with (17/128 = 13%) ioPTH. The overall disease control (eucalcemia) rate was 95%. 3/111 (3%) of patients who had surgery without ioPTH measurements required re-exploration. Conclusions Selective use of ioPTH is an effective strategy. ioPTH is best reserved for patients who have non-localizing preoperative imaging, are at risk for multi-gland disease, or require revision surgery.